Capillary isoelectric focusing of native and inactivated microorganisms - Horká, M; Kubícek, O; Růzicka, F; Holá, V; Malinovská, I; Slais, K (Journal of chromatography. A, 2007)
The research of microorganisms includes the development of methods for the inactivation of viruses and other microbes. It also means to efficiently eliminate the infectivity of microorganisms without damage of their integrity and structure. According to the results of the last 5 years the capillary electromigration techniques appear to be very perspective for the comparison of the methods applicable for inactivation in the diagnostics and study of the pathogens. In this paper we suggest the capillary isoelectric focusing of the model microorganisms, Escherichia coli, Staphylococcus epidermidis, Candida albicans and bacteriophage PhiX 174, native or inactivated by different procedures. UV detection and fluorometric detection for the dynamically modified microbes by pyrenebutanoate on the basis of the non-ionogenic tenside were used here. Isoelectric points of native and/or dynamically modified microorganisms and other properties were compared with those obtained after microorganisms inactivation. The segmental injection of the sample pulse enabled the reproducible and efficient capillary isoelectric focusing in different pH gradients. The low-molecular-weight pI markers were used for tracing of the pH gradient.
Keywords: Staphylococcus epidermidis; Isoelectric Focusing; isoelektrická fokusace; Candida albicans; povrchově aktivní látky; Bacteriophage phi X 174; izoelektrický bod; Pilot Projects; Electrophoresis, Capillary; Bacteria; Escherichia coli; mikrobiální viabilita; Microbial Viability; pilotní projekty; elektroforéza kapilární; Isoelectric Point; Surface-Active Agents; bakteriofág phi X 174